Predictors of Students’ Environmentally Friendly Behavioral Intention: A Theory of Planned Behavior-Based Analysis - Anita Novilia; Agus Sugiarto (Kelola: Jurnal Manajemen Pendidikan, 2025)
Adiwiyata is a program that is oriented towards forming schools that care about and have an environmental culture by integrating environmental education into the curriculum, extracurricular activities, and school management. The main output is to form more environmentally friendly student behavior. This study aims to examine the influence of attitudes, subjective norms, and behavioral control on behavioral intentions and their impact on students' environmentally friendly behavior. The study was conducted using an explanatory approach with 187 respondents taken using purposive sampling techniques. The analysis and hypothesis testing techniques used Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings show that attitudes, subjective norms, and behavioral control perceived by students have a positive influence on students' intentions to engage in environmentally friendly behavior, which in turn, behavioral intentions have a positive effect on their environmentally friendly behavior at school and in their environment.